Justice for Tajudin: Proposal of Legal Aid for the Poor: Keadilan untuk Tajudin: Rancangan Bantuan Hukum bagi Masyarakat Miskin - Dhimas Danu Wicaksana; Rizky Pratama Aristya Putra; Wisnu Wibawanto Dwi Putra; Mahendra Pratama Putra; Muhammad Agung Dimas Widtono (The Indonesian Journal of International Clinical Legal Education, 2022)
Tajudin has been in prison for 9 months. The police charged Tajudin with the Criminal Act of Trafficking in Persons with a threat of 15 years in prison. This is because the police consider Tajudin to be exploiting children, by employing a 14-year-old cepi and Dendi to help sell his wares. After going through a series of long processes, the files went to court. The prosecutors demanded that Tajudin was trafficking in persons and demanded 3 years in prison. Not only that, the prosecutor also asked Tajudin to pay a fine of Rp. 120 million.